Microneedles loaded with glutathione‐scavenging composites for nitric oxide enhanced photodynamic therapy of melanoma - Fan Jia; Weijiang Yu; Xinfang Li; Yonghang Chen; Youxiang Wang; Jian Ji (Bioengineering & Translational Medicine)
Abstract Photodynamic therapy (PDT) represents an attractive promising route for melanoma treatment. However, its therapeutic efficacy is compromised by inefficient drug delivery and high glutathione (GSH) levels in cancer cells. To overcome these challenges, microneedles (MNs) system loaded with GSH‐scavenging nanocomposites was presented for nitric oxide (NO) enhanced PDT. The nanocomposites consisted of S‐nitroso‐N‐acrylate penicillamine (SNAP; a NO donor) grafted fourth‐generation polyamide amine dendrimer (G4) and chlorin e6 (Ce6). Upon local insertion of polyvinylpyrrolidone MNs, G4‐SNAP/Ce6 composites were fast delivered and significantly amplified the therapeutic effects during PDT, via GSH depletion and reactive nitrogen species generation. Even with a single administration and low power light exposure, MNs with G4‐SNAP/Ce6 effectively halt the tumor progression. The system demonstrated better cancer ablation efficacy than Ce6 alone toward melanoma. The strategy may inspire new ideas for future PDT‐related therapy for skin tumors.